Pediatric Bowel Management Options and Organizational Aspects - Elizaveta Bokova; Wendy Jo Svetanoff; Marc Aaron Levitt; Rebecca Maria Rentea (MDPI AG, 2023)
A bowel management program (BMP) to treat fecal incontinence and severe constipation is utilized for patients with anorectal malformations, Hirschsprung disease, spinal anomalies, and functional constipation, decreasing the rate of emergency department visits, and hospital admissions. This review is part of a manuscript series and focuses on updates in the use of antegrade flushes for bowel management, as well as organizational aspects, collaborative approach, telemedicine, the importance of family education, and one-year outcomes of the bowel management program. Implementation of a multidisciplinary program involving physicians, nurses, advanced practice providers, coordinators, psychologists, and social workers leads to rapid center growth and enhances surgical referrals. Education of the families is crucial for postoperative outcomes, prevention, and early detection of complications, especially Hirschsprung-associated enterocolitis. Telemedicine can be proposed to patients with a defined anatomy and is associated with high parent satisfaction and decreased patient stress in comparison to in-person visits. The BMP has proved to be effective in all groups of colorectal patients at a 1- and 2-year follow-up with social continence achieved in 70-72% and 78% of patients, respectively, and an improvement in the patients' quality of life. A transitional care to adult program is essential to maintain the same quality of care, and continuity of care and to achieve desired long-term outcomes as the patient reaches adult age.